2019
DOI: 10.1371/journal.pone.0216827
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale implementation of standardized quantitative real-time PCR fecal source identification procedures in the Tillamook Bay Watershed

Abstract: Fecal pollution management remains one of the biggest challenges for water quality authorities worldwide. Advanced fecal pollution source identification technologies are now available that can provide quantitative information from many animal groups. As public interest in these methodologies grows, it is vital to use standardized procedures with clearly defined data acceptance metrics and conduct field studies demonstrating the use of these techniques to help resolve real-world water quality challenges. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The value of fecal indicators as investigative tools to identify fecal pollution has been reaffirmed and expanded with the broad adoption of MST approaches, despite imperfect sensitivity and specificity [ 58 , 81 , 110 , 118 •, 119 ]. Also, the literature on many technical aspects of fecal indicators and their applications has notably matured, as demonstrated by the recent publication of several comprehensive reviews [ 2 •, 17 , 25 , 27 , 44 , 144 , 153 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The value of fecal indicators as investigative tools to identify fecal pollution has been reaffirmed and expanded with the broad adoption of MST approaches, despite imperfect sensitivity and specificity [ 58 , 81 , 110 , 118 •, 119 ]. Also, the literature on many technical aspects of fecal indicators and their applications has notably matured, as demonstrated by the recent publication of several comprehensive reviews [ 2 •, 17 , 25 , 27 , 44 , 144 , 153 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches increase the complexity, expense, and time requirements for analysis, and physical removal of inhibitors through dilution or purification also reduces target DNA, providing diminishing returns to analytical sensitivity [ 147 , 148 ]. Complete abatement of qPCR inhibition is likely unrealistic; nevertheless, recent efforts to standardize qPCR procedures for water quality assessment suggest that a set of existing mitigation practices is sufficient to render matrix interference a manageable nuisance in most applications [ 81 , 144 , 149 •]. Increasing adoption of digital PCR (dPCR), a quantitative PCR approach robust to inhibition, will likely further alleviate the challenge of inhibition for routine molecular detection of fecal microbes [ 61 , 114 , 128 , 150 – 152 ].…”
Section: Molecular Methods: Challenges and Advancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven of these samples approached the LOD 95 of the Open qPCR thermocycler, and CBM partners detected one of these samples. This is a common issue in PCR based fecal source tracking studies, not just in CBM studies, and highlights the importance of ensuring a particular method fits the research question, especially in a CBM study [33]. Nonetheless, a recent study found that an HF183 gene copy number of 4200 HF183/100ml exceeds the USEPA benchmark risk of GI illness [10].…”
Section: Agreement Between Cbm Partners and Scientistsmentioning
confidence: 99%